An artificial accelerogram generator code written in Matlab. Issue 3 (2nd March 2020) - Ferreira, Fernando; Moutinho, Carlos; Cunha, Álvaro; Caetano, Elsa
ABSTRACT: Artificial accelerograms are a very useful tool for designing structures against seismic hazards; in particular, when structures exhibit nonlinear behavior. This paper presents a Matlab code for generating artificial accelerograms to match code‐defined spectra based on the modification of actual earthquake ground motions. In this case, while the code is written to generate Eurocode 8‐compatible accelerograms, it can be easily adapted to any other code in the world. The proposed code determines the earthquake spectra and Fourier Transform using the Fast Fourier Transform algorithm and then modifies the Fourier Transform in order to match the predefined spectra. The code also includes instructions for outlining different actual ground motions, soil, and earthquake type. The code is geared to students and researchers in the field of Structural and Earthquake Engineering. The objective of this work is to provide a Matlab code that can be integrated in other research programs such as seismic structural analysis, structural control software, or other codes. Abstract : A simple algorithm is used to match an original event to a Eurocode 8‐defined spectra. The algorithm is written in a Matlab code that intends to be distributed and be easily integrated in other research programs.